Exercise-induced hypoalgesia and intensity of exercise - Koltyn, K. F. (Sports Medicine, 2002)
Pain sensitivity has been found to be altered following exercise. A number of investigators have found diminished sensitivity to pain (hypoalgesia) during and following exercise. However, currently it is unknown whether there is a specific intensity of exercise that is required to produce this hypoalgesia response. Aerobic exercise, such as cycling and running, have been studied most often, and a number of different exercise protocols have been used in this research including: (i) increasing exercise intensity by progressively increasing the workloads; (ii) prescribing a particular exercise intensity based on a percentage of maximum; and (iii) having participants self-select the exercise intensity. Results indicate that hypoalgesia occurred consistently following high-intensity exercise. In the studies in which exercise intensity was increased by increasing workloads, hypoalgesia was found most consistently with a workload of 200W and above. Hypoalgesia was also found following exercise prescribed at a percentage of maximal oxygen uptake (e.g. 60 to 75%). Results are less consistent for studies that prescribed exercise based on percentage of heart rate maximum, as well as for studies that let participants self-select the exercise intensity. However, there has not been a systematic manipulation of exercise intensity in most of the studies conducted in this area. In addition, the interaction between exercise intensity and exercise duration, more than likely influences whether hypoalgesia occurs following exercise. There is a need for research to be conducted in which both intensity and duration of exercise are manipulated in a systematic manner to determine the 'optimal dose' of exercise that is required to produce hypoalgesia. In addition, there is a need for more research with other modes of exercise (e.g. resistance exercise, isometric exercise) to determine the optimal dose of exercise required to produce hypoalgesia.